2011
DOI: 10.1007/s11141-011-9247-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of modification of a high-latitude ionosphere by high-power HF radio waves. Part 1. Results of multi-instrument ground-based observations

Abstract: We present the results of multi-instrument experiments related to studying the phenomena in the high-latitude ionosphere affected by high-power radio waves using the EISCAT technical facilities. It was found for the first time that strong small-scale artificial field-aligned irregularities (AFAIs) are excited when the ionospheric F region is heated by a high-power HF radio wave with X-mode polarization near the altitude at which the critical frequency f xF 2 of the F 2 layer is equal to the frequency f H of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The growing body of X‐mode experiments at the EISCAT (European Incoherent Scatter) Scientific Association HF heating facility with the use of various multi‐instrument diagnostics showed that extraordinary (X‐mode) powerful HF radio waves are capable of producing a strong modification of the high latitudinal ionospheric F region, including the generation of the artificial field‐aligned irregularities (FAIs) (Blagoveshchenskaya, Borisova, Yeoman, Rietveld, ; Blagoveshchenskaya, Borisova, Yeoman, Rietveld, Ivanova, et al, ; Blagoveshchenskaya et al, ), optical emissions at red (630 nm) and green (557.7 nm) lines (Blagoveshchenskaya et al, ), and various spectral components in the narrowband stimulated electromagnetic emission spectra (Blagoveshchenskaya et al, ). Considerable study has been given to the HF‐enhanced ion and plasma lines (HFILs and HFPLs) from the EISCAT UHF incoherent scatter radar spectra excited under X‐mode heating, which are the signatures of the ion acoustic (IA) and Langmuir (L) electrostatic waves (Blagoveshchenskaya et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The growing body of X‐mode experiments at the EISCAT (European Incoherent Scatter) Scientific Association HF heating facility with the use of various multi‐instrument diagnostics showed that extraordinary (X‐mode) powerful HF radio waves are capable of producing a strong modification of the high latitudinal ionospheric F region, including the generation of the artificial field‐aligned irregularities (FAIs) (Blagoveshchenskaya, Borisova, Yeoman, Rietveld, ; Blagoveshchenskaya, Borisova, Yeoman, Rietveld, Ivanova, et al, ; Blagoveshchenskaya et al, ), optical emissions at red (630 nm) and green (557.7 nm) lines (Blagoveshchenskaya et al, ), and various spectral components in the narrowband stimulated electromagnetic emission spectra (Blagoveshchenskaya et al, ). Considerable study has been given to the HF‐enhanced ion and plasma lines (HFILs and HFPLs) from the EISCAT UHF incoherent scatter radar spectra excited under X‐mode heating, which are the signatures of the ion acoustic (IA) and Langmuir (L) electrostatic waves (Blagoveshchenskaya et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…) [21,31,33,35,37]. It is important to note that X-mode artifi cial fi eld-aligned irregularities are generated in the regular F region under quiet conditions (no precipitation of particles, fi eld-aligned currents, and electrojet).…”
Section: Small-scale Artifi Cial Field-aligned Irregularities (Afais)mentioning
confidence: 99%
“…Features and behaviors of artifi cial fi eld-aligned irregularities, stimulated electromagnetic emission, electron temperature and density, Langmuir and ion-acoustic plasma waves, seen from the incoherent-scatter radar as HF-induced plasma and ion lines, were analyzed in the course of pump-wave frequency stepping within 200 kHz of the ce nf . Such investigations were made for third [20,21], fourth [22], fi fth, and sixth [23] electron gyro-harmonics. Distinctive features, possible generation mechanisms, and conditions of appearance of outshifted plasma lines were considered in [24].…”
Section: Introductionmentioning
confidence: 99%
“…The modeling of the excitation of low-frequency waves in HF heating discussed above uses an ionospheric profile, shown in Figure 3.1, that does not include small-scale features, such as straiations and Rietveld et al [2003] directly verify the increase in electron temperature by 3000 K whereas the ion temperature was enhanced only by 100 K. Later experiments by Blagoveshchenskaya et al [2011] show electron temperatures reaching close to 6000 K when the HF pump approaches magnetic zenith. Although the experimental facilities at HAARP cannot directly measure electron temperature, they have been able to detect descending artificial ionized layers (DAIL) [Pedersen et al, 2009], the generation and descent of which were modeled extensively by , indicating that the DAILs required bulk heating of the electrons to ~4000 K to be subsequently accelerated by Langmuir turbulence to suprathermal speed and ionize the neutrals.…”
Section: Kinetic Processes In Hf Heatingmentioning
confidence: 99%